Codigestão anaeróbia de resíduos pecuários e agroindustriais em reatores do tipo CSTR - Enokida, Cristina Harumi (2024)
Increased consumption of animal proteins in recent years has driven production and, consequently, increased the generation of waste rich in organic matter. In addition to the agroindustry, stages of protein processing on farms also generate waste that requires treatment, preferably at the point of origin, to avoid long-distance transportation. To reduce costs and optimize production, it is essential to adopt technologies that also ensure proper management of these wastes. One treatment alternative already used in the country is Anaerobic Digestion (AD), which removes a significant portion of the organic matter from the waste, generating biogas and digestate, which has potential use as a biofertilizer. This study evaluated the anaerobic digestion of five different wastes from livestock activities (cattle manure, swine manure, and bird hatchery waste) and agro-industrial activities (bone and protein waste, and dry sludge from Dissolved Air Flotation – DAF) in a laboratory-scale Continuous Stirred Tank Reactor (CSTR). Different mixtures of waste were tested in the reactor, characterizing a co-digestion process, with the aim of identifying the best operational conditions considering the availability of waste. The reactor used had a useful volume of 12L and an operational volume of 17L, with an agitation system adjusted to a regime of 65 rpm, operating 20 minutes off and 5 minutes on, with heating maintained at 37°C. Initially, the reactor was fed only with swine and cattle manure, with the subsequent load progression of other wastes, totaling seventeen experimental phases. During the study, physical, chemical, and biological parameters of the wastes and reactor biomass were analyzed, as well as productivity and biogas yield calculations. The results indicated that the best Volumetric Organic Loading Rate (OLR) was obtained in the ninth phase, reaching3,67 kgSVadic m⁻³ d⁻¹, with a productivity of 2,84 LN Lreator⁻¹ d⁻¹ and a yield of 770 LN kgSVadic⁻¹ d⁻¹ of biogas. Microbiological analyses in selected phases identified the predominance of bacterial phyla associated with hydrolysis and acidogenesis, especially Firmicutes. The acidogenic genus Clostridium sensu stricto_1 was predominant in Phase VII, while DTU014 (acetogenic) stood out in Phase XIV. Methanogenesis, initially conducted by Methanosaeta via acetoclastic (Phase V), was later replaced by Methanosarcina, coinciding with the accumulation of volatile fatty acids (VFAs). Finally, the data obtained provided robust information for the replication of the process on a full scale, serving as a basis for the development of an optimized biogas plant according to the experimental conditions established in the laboratory.